Knowledge of Postpartum Mothers about Kegel exercises for Perineal Wound Healing - Siregar, Rya Anastasya; Novita Sari Batubara; Rizka Heriansyah; Lubis, Tapi Endang Fauziah; Harahap, Maryam Latifah (PT Inovasi Pratama Internasional, 2024)
The World Health Organization reported 2.7 million perineal injuries in women giving birth in 2009, reaching 6.3 million in 2020. A study was conducted to determine postpartum mothers' knowledge about kegel exercises to prevent perineal wounds. The study involved 30 respondents, with 83% having less knowledge than others. The majority had less knowledge of housework, tertiary education, and health workers. The study suggests that more knowledge is needed from health workers, electronic media, and print media. Respondents' knowledge about Kegel exercises for healing perineal wounds was based on information sources, the majority had little knowledge with health workers as many as 15 people (50%) and the minority had enough knowledge with electronic media as many as 2 people (7%).